2020
DOI: 10.1002/ags3.12334
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis in the clinical management of biliary tract cancer

Abstract: Biliary tract cancer (BTC) is clinically and pathologically heterogeneous and responds inadequately to treatment. A small section of patients develop resectable disease, although the relapse rates are high; the benefits of adjuvant capecitabine chemotherapy for BTC are now understood, and gemcitabine‐based combination chemotherapy is the first line of therapeutic strategy for BTC; however, alternative therapy for BTC is not known. Genomic profiling can provide detailed information regarding the carcinogenesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 76 publications
(217 reference statements)
0
8
0
Order By: Relevance
“…Recently, the development of genomic sequencing in BTC has rapidly progressed, and favorable treatment effects of molecular targeting agents, such as isocitrate dehydrogenase-1 inhibitors and fibroblast growth factor receptor inhibitors, in BTC, have been reported (17)(18)(19). Furthermore, the development of immune checkpoint inhibitors is promising, and for tumors with high microsatellite instability, pembrolizumab can be administered for multiple cancer types in various organs, including BTC (20).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the development of genomic sequencing in BTC has rapidly progressed, and favorable treatment effects of molecular targeting agents, such as isocitrate dehydrogenase-1 inhibitors and fibroblast growth factor receptor inhibitors, in BTC, have been reported (17)(18)(19). Furthermore, the development of immune checkpoint inhibitors is promising, and for tumors with high microsatellite instability, pembrolizumab can be administered for multiple cancer types in various organs, including BTC (20).…”
Section: Discussionmentioning
confidence: 99%
“…KRAS mutations occur in ∼9%-40% of CCAs, 83 with some of these being KRAS G12C mutations. The phase I/II KRYSTAL-1 study examined the use of adagrasib, a KRAS G12C inhibitor, in patients with advanced solid tumors harboring a KRAS G12C mutation.…”
Section: Molecular and Genomic Profile Of Ccamentioning
confidence: 99%
“…Despite approval for use in patients with >10 mut/mb, much debate exists around tumor mutational burden (TMB) and its use as a predictor of response to immunotherapy. Genomic assessment of 412 BTC revealed that 11% had germline mutations in genes associated with the development of a high tumor mutational burden (RAD51D, MLH1, MSH2, POLD1, POLE and ATM), making it an attractive biomarker to assess [ 31 ]. In other disease subtypes, however, when MSI-high is excluded from the analysis of patients with high-TMB, its predictive value appears to be limited [ 32 ].…”
Section: Immunotherapymentioning
confidence: 99%